'A Force for Good': The Narrative Construction of Ethical EU–Vietnam Trade Relations. (5th December 2021) - Nessel, Camille; Verhaeghe, Elke
Abstract: Political representation of problems includes an aim to control an audience's impressions and create a societally‐acceptable social reality. This paper analyses the narrative construction of ethical trade between the European Union (EU) and Vietnam. As an undemocratic Other, Vietnam has been sharply criticized for its human rights record by civil society and Members of European Parliament. Yet, the EU recently concluded two trade agreements with Vietnam. We argue that, unchallenged by the European Parliament, the European Commission created a performative 'story of change' for its European audience by simultaneously appealing to underlying 'neoliberal' and 'development' paradigms. In this narrative, the EU and Vietnam star as the main characters, who, in their joint attempts to make bilateral trade 'a force for good', live moments of heroism, encounter fleeting instances of victimhood, and defeat villains on the path to ethical trade.